Anosmia in dementia is associated with Lewy bodies rather than Alzheimer's pathology. Issue 6 (1st June 2001) - McShane, R H; Nagy, Z; Esiri, M M; King, E; Joachim, C; Sullivan, N; Smith, A D
Abstract : OBJECTIVES: To assess olfactory function of patients with dementia. Odour detection ability is impaired in clinical Parkinson's disease. Evidence of impaired detection in patients with clinically diagnosed Alzheimer's disease is inconsistent. No studies of olfaction have been neuropathologically validated. METHODS: The olfactory function of 92 patients with dementia and 94 controls was assessed using a simple bedside test as part of the Oxford Project To Investigate Memory and Ageing (OPTIMA). Neuropathological assessment was made of cortical Lewy bodies and substantia nigra (SN) cell counts and of Alzheimer's disease in all 92 patients, 22 of whom had SN Lewy bodies and 43 of whom had only Alzheimer's disease. RESULTS: Patients with Lewy bodies were more likely to be anosmic than those with Alzheimer's disease or controls. Patients with Alzheimer's disease were not more likely to be anosmic than controls. Nor was anosmia associated with degree of neurofibrillary tangles, as assessed by Braak stage. Among subjects with Lewy bodies, overall cortical Lewy body scores and Lewy body density in the cingulate were higher in those who were anosmic. Consensus clinical criteria for dementia with Lewy bodies had a sensitivity of 64% and specificity of 89%. In the absence of definite Alzheimer's disease, the criteria had sensitivity of 100%. In patients with definite Alzheimer's disease, anosmia was slightly more sensitive (55%) than the consensus criteria (33%). However, the addition of anosmia to the consensus criteria did not improve their overall performance. CONCLUSION: Dementia with Lewy bodies is associated with impaired odour detection. Misdiagnosis may have accounted for some previous reports of impaired odour detection in Alzheimer's disease. Simple but more sensitive tests of anosmia are required if they are to be clinically useful in identifying patients with dementia with Lewy bodies.